2004
DOI: 10.1210/jc.2003-032002
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Dietary Iodine: Bread, Cows’ Milk, and Infant Formula in the Boston Area

Abstract: Dietary iodine is essential for thyroid hormone production. Although U.S. dietary iodine is generally adequate, some groups, especially women of childbearing age, are at risk for mild iodine deficiency. Children's average urinary iodine is higher than that of adults. U.S. dietary iodine sources have not been assessed recently. A survey of iodine content in 20 brands of bread, 18 brands of cows' milk, and eight infant formulae was performed between 2001 and 2002. Three bread varieties contained more than 300 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(151 citation statements)
references
References 10 publications
9
140
1
1
Order By: Relevance
“…Table 9 compares iodine concentrations for three foods as reported in the literature to findings in similar TDS foods. The iodine concentrations in milk reported by Kirk et al (2005) were considerably lower than either the TDS samples or those reported by Pearce et al (2004), but TDS iodine levels in infant formula and bread were consistent with those reported in the literature. These TDS results increase substantially the available data for characterizing dietary exposure to perchlorate and provide a useful basis for the beginning to evaluate overall perchlorate and iodine estimated dietary intakes in the US population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Table 9 compares iodine concentrations for three foods as reported in the literature to findings in similar TDS foods. The iodine concentrations in milk reported by Kirk et al (2005) were considerably lower than either the TDS samples or those reported by Pearce et al (2004), but TDS iodine levels in infant formula and bread were consistent with those reported in the literature. These TDS results increase substantially the available data for characterizing dietary exposure to perchlorate and provide a useful basis for the beginning to evaluate overall perchlorate and iodine estimated dietary intakes in the US population.…”
Section: Discussionsupporting
confidence: 87%
“…Perchlorate and iodine levels in selected foods have been reported previously in the literature (Pearce et al, 2004;Jackson et al, 2005;Kirk et al, 2005;Sanchez et al, 2005a, b;Sanchez et al, 2006). In addition, FDA conducted exploratory surveys in 2004 and 2005 to determine perchlorate levels in selected foods.…”
Section: Discussionmentioning
confidence: 81%
“…Generally, less than 5% of perchlorate exposure was estimated to be from pasta derived from durum wheat, regardless of the population group. Overall, the trends generally agree with national estimates reported by Murray et al, 2008. Although milk is estimated to be the single largest source of perchlorate to total exposure, it is also a significant source of protein, vitamins and nutrients (Wattiaux, 1999), including iodide (Pearce et al, 2005). Similarly, vegetable and fruit crops are a significant source of nutrients and vitamins for Americans accounting for 35, 25 and 16% of average consumption of vitamin A, vitamin C, and dietary fiber, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…iodine-containing detergents used in the dairy industry. 47,4 It is not mandatory to use iodised salt for the production of processed food in South Africa, and most producers use non-iodised salt in their products to prevent unwanted effects of iodine on the properties of their product, for health reasons and financial considerations. 49 Despite these fears, substantial amounts of iodine, namely 39-69 ppm, were found in the salt of one-third (4 out of 12) of manufactures of bread, margarine and flavourants of salty snacks in South Africa.…”
Section: Iodine In Processed Foodsmentioning
confidence: 99%